Changes in the Correlates for Intimate Partner Violence Against Women in Vietnam: Evidence From the 2010 and 2019 National Prevalence Surveys - Vyas, Seema (Violence against women, 2023)
This study sought to understand whether the risk and protective factors associated with current partner violence changed in Vietnam using findings from two comparable surveys conducted in 2010 and 2019. Fifteen (2010) and 17 (2019) factors were significantly associated with violence, and the level of consistency was high—nonpartner sexual violence, respondent and partner prior abuse, men's expressions of masculinity, and indicators of low economic status continue to put women at risk. Gender-transformative approaches that address power inequalities, foster positive parenting, and promote the political and social influence of women are required and should be adapted to the Vietnam context.